Perception of medical health care practitioners and health care consumers towards traditional health care systems in western Ladakh, India - Angmo, Kunzes; Gailson, Lotos; Adhikari, Bhupendra S; Bussmann, Rainer W.; Rawat, Gopal S (Ethnobotany Research and Applications, 2023)
Background: This study focussed on the perception of Medical Health Care Professionals (MHCPs) and Local Health Care Consumers (LHCCs) on traditional health-care systems (THCS) and collaboration of both traditional and modern health-care system in western Ladakh, India. Methods: The study area was based on the distribution of three different socio-cultural groups in three valleys (Lower Indus, Suru and Wakha Chu) in western Ladakh. A detailed field investigation was undertaken for the perception, which involved semi-structured questionnaire survey of 30 MHCPs and 540 LHCCs, to document their opinion regarding integration of traditional and modern medicine. Results: Although local communities comprehend health problems and solutions within their cultural frame of reference but now it has changed over the years. The majority of MHCPs and LHCCs were agreed on the collaboration of both the health care systems. Conclusions: Of all the THCS the Amchi system seems to be the most scientific and therefore the most logical one to be integrated into the modern medicine system. Keywords: Age class, Amchi system, Akhons, Shamans Lower Indus valley, Sowa-rigpa, Suru-valley